THE POETIC HARMONY OF RHYME AND MEANING IN ALISHER NAVOI’S “LAYLI AND MAJNUN” - Shohsanam Abdumannapova (Western European Studies, 2025)
The article explores the relationship between the rhyme elements used in Alisher Navoi’s epic “Layli and Madjnun” and the content of the work. Several chapters of the poem are analyzed in detail. The number and forms of rhymes used in the poem are identified, with specific couplets examined separately. The overall findings are systematically presented in the form of tables. The role of different types of rhyme in conveying the author’s ideas is also discussed.
Keywords: meter; rhyme; muqayyad